Evaluasi Penerapan Dan Pelaksanaan Tiket Elektronik Lintas Tanah Abang-Serpong - Rita, Rita; Sinaga, Rosita (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Electronic tickets for the cross Tanah Abang-Serpong imposed on July 4,2007 to train KRL ACEconomy Economy, similnr with tire innugurntion of double tmck hy tire President of tlze Republic ofIndonesia (Susilo Bmnbang )'udm;ono). /111plt'1111'11t11t1011 of electronic tickets do not lnst ven; longonly about two weeks, caused m; the electronics ticket mnclzines were dnmaged in the reporting ofinformation si;sterns to the financial section.77ius,the ticket/train ticket cross Tanah Abang-Serpong returned to the origi.nnl SIJStem that is m;selling tickets mnnuall. Haweuer, Directorate General of Rnilwm;s promised in the near future implementationof electronic tickets will be reintroduced mrd is rnrrenlly still prosess fn; PT. Kereta Commuter]abotabek (PT. KC]).Keywords : Electronic Ticket, Implementation nnd Operation